Tirupati caritramu : Śrī Vēṅkaṭācalapati ālayamu : anuvādasaṅgrahamu - Viraraghavacharya, T. K. T. (Tirumala Tirupati Dēvasthānamulu, 1978)
Telugu rendering of an English work about Tirupati, Vaishnavite pilgrimage center, Andhra Pradesh.